Inhibitory mechanism on tyrosinase activity of flavonoids from flower buds of Sophora japonica L - Yunfeng Ma; Chaoyang Zhang; Jinlin Li; Jiayan Xiong; Bao-Lin Xiao (Heliyon)
The flower buds of Sophora japonica L. (FBSJ) have long been applied as Traditional Chinese Medicine (TCM) and functional food in East Asia. In this study, extracts of FBSJ from 11 different locations were analyzed using the HPLC method to establish their HPLC fingerprints. By determining the IC50 on tyrosinase activity, it was discovered that the extract from Kunming, Yunnan Province exhibited the strongest inhibitory activity. Further analysis, including partial least squares regression coefficient analysis and grey correlation analysis, regarded kaempferol, isorhamnetin, and quercetin as the compounds with significant tyrosinase inhibitory activities. To understand the inhibition mechanism of tyrosinase activity, various analytical techniques such as enzymatic kinetic analysis, fluorescence quenching, circular dichroism (CD), molecular docking, and molecular dynamics simulation were employed. The results revealed that quercetin, isorhamnetin, and kaempferol exhibited higher inhibitory activity and binding energy compared with kojic acid, indicating their potential value as natural tyrosinase inhibitors. This research provides a solid theoretical foundation for studying the application and mechanism of flavonoids against tyrosinase in FBSJ.